400 GENETIC DISSECTION OF FEMORAL BONE STRENGTH IN MICE. (1st January 2005) - Vanek, C.; Kansagor, J. N.; Munsey, T.; Olson, D. A.; Belknap, J. K.; Shea, M.; Orwoll, E. S.; Klein, R. F.
Abstract : Background: Bone strength and thus, the likelihood of fracture, is a complex trait likely influenced by a number of different genes. The number, locations and effects of the individual genes contributing to natural variation in skeletal fragility are all unknowns. Methods: To begin to identify the heritable determinants of bone strength, we have examined femoral shaft failure load (FL) in a genetically heterogeneous F2 population of mice (N=997) derived from C57BL/6 (B6) and DBA/2 (D2) inbred progenitor strains. Femora from sixteen-week-old mice were harvested and tested to failure in 3-point bending. Mice were genotyped with microsatellite markers chosen from the MIT database at an average spacing of 15 centiMorgans (cM). Results: Genome-wide quantitative trait locus (QTL) analysis of the B6D2F2 population revealed regions on five different chromosomes that were very strongly linked to FL (chromosomes 3, 7, 8, 14, and 17) in both genders. Evidence of gender-specific genetic influences on FL was also identified at three other chromosomal sites (chromosomes 2, 12, and X). It is interesting to note that the chromosome 2, 3, 8, 12, 14, and 17 QTLs identified here contain genomic regions thought to be homologous with 20p, 1q, 16q, 2p, and 13q regions of the human genome that are associated with osteoporosis risk. Conclusions: These results suggest that the genetic determinants of the complex phenotype of skeletal fracture can be effectively studied by analysis of primary skeletal characteristics. The identification of the genes responsible for biomechanical differences in murine skeletal development should reveal fundamentally important processes in the control of skeletal integrity. Based on the considerable linkage conservation between mouse and human genomes, findings in this animal model should aid in the identification of specific osteoporosis candidate genes for study in human populations.